Analisis Kebutuhan Pelatihan bagi Tenaga Administrasi di Instalasi Rawat Jalan RSD dr.Soebandi Jember (Training Need Analysis for Administratrive Staffs in Outpatient Installation at RSD dr.Soebandi Jember) - Anita Krisdiyanti; Nuryadi Nuryadi; Christyana Sandra (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Training need analysis is the process of collecting and analyzing data to identify the factors that need to be improved with training. In 2009, RSD dr.Soebandi Jember has conducted a training needs analysis for administrative staffs using based Job Competencies Based Need Analysis approach. However, it would be appropriate if the RSD dr.Soebandi Jember uses Person Competencies Based Need Analysis approach so can be identified that the gap between the standard and actual competency. The objective of these study was to analyzed the training needs for administrative staffs in Outpatient Installation at RSD dr.Soebandi with Person Competencies Based Need Analysis approach. These study used a descriptive research. Based on these research, competency standards of knowledge, attitude, and skill consist of excellent service, administrative, computer, and SIM-RS. In addition, it was determined those all or 100% of administrative staffs in Outpatient Installation must met the standards of competency in both categories. In actual competency was found that the administrative sttafs who had good knowledge are 43%, good attitude are 91%, and good skill are 45%. Based on results of the identification of standard competency and actual competency can be concluded that on average there was a gap on all competency. Keywords: Training Need Analysis, Person Competencies Based Need Analysis